(untitled) (Journal of Atomic and Molecular Sciences, 2010)
In a recent calculation on K_α transition properties of fluorine-like ions (10 ≤ Z ≤ 79) by Sur et al. [Phys. Rev. A 77 (2008) 052502], it was found that there is a crossover between K_α1 and K_α2 transition probabilities with increasing of atomic number Z. In order to examine this unusual behavior, a further theoretical study has been carried out by using multi-configuration Dirac-Fock (MCDF) method. In the calculation, Breit interaction, electron correlation and quantum electrodynamics (QED) effects have been included. The present study shows a contrary conclusion to the earlier theoretical results.